A Conceptual Study on Teachers’ Leadership Values - Eric Hermawan; Naufal Mahfudz; Cris Kuntadi; Antoni Ludfi Arifin; Antaiwan Bowo Pranogyo (STAI Hubbulwathan Duri, 2023)
This study aims to undertake a conceptual analysis of the leadership principles exhibited by a teaching staff, focusing on six key aspects: concentration, open-mindedness, respect, striving for excellence, being the best, and integrity. This study is a theoretical examination of the leadership principles exhibited by educational faculty. This study employs a qualitative descriptive approach. The data was collected from scientific journal articles written in English and Indonesian. The databases that were searched include CiteBase, Cybertesis, Dissertation Library, and ProQuest. The selected publications were thoroughly examined, including the abstract, data analysis, methodologies, and aims, in order to acquire information about the significance of leadership in teaching staff. The findings show that the goal of leadership is to direct and focus. Leaders must be self-directed to achieve this. The teacher must focus ourselves and connect constructively with others. This helps leaders in education improve emotional intelligence. A responsive mentality can help teachers adapt and handle unusual assignments and colleagues. Respectful teaching staff leadership means treating everyone with respect and real attention, regardless of rank, status, or position. Excellence requires constant effort and the pursuit of the highest work standards. Excellence in leadership means achieving excellent team performance while giving support, direction, and growth opportunities to colleagues, motivating and inspiring them. Teacher integrity is essential for a school or college's success. Leadership principles strongly influence an educator's beliefs, actions, and decisions.